Management of the Mosque Prosperity Board (BKM) of Raya Al Husain Mosque in Martubung Subdistrict in Attracting Public Interest in Performing Fajr Prayer - Marwan Marwan; Muhammad Putra Dinata Saragi (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines the management practices of the Mosque Prosperity Board (BKM) at Raya Al Husein Mosque in attracting congregational participation in Fajr prayer. Despite the central role of congregational worship in Islam, participation rates remain relatively low, particularly in urban and semi-urban contexts. This research employs a qualitative case study approach, using observation, in-depth interviews, and documentation to explore how mosque management is experienced by congregants. Data were analyzed through coding procedures, including open, axial, and selective coding, to identify key themes. The findings reveal that participation is not solely influenced by religious obligation or facility availability, but emerges from a multidimensional experiential process. Four interrelated dimensions were identified: physical comfort, psychological and affective comfort, behavioral transformation, and experiential meaning. Comfort functions as a central construct that mediates the relationship between environmental conditions and congregational behavior. Physical improvements shape initial perceptions, which are then internalized into psychological comfort, fostering intrinsic motivation and leading to sustained participation. This study contributes by proposing an integrative model in which mosque management operates as a process of designing meaningful religious experiences. The findings highlight the importance of shifting from conventional management approaches toward more holistic and experience-oriented strategies to enhance congregational engagement.